TGF-β signaling alters the pattern of liver tumorigenesis induced by Pten inactivation - Morris, Shelli M. (Oncogene, 2014)
Hepatocarcinogenesis results from the accumulation of genetic and epigenetic changes in liver cells. A common mechanism through which these alterations induce liver cancer is by deregulating signaling pathways. A number of signaling pathways, including the PI3K/PTEN/AKT and transforming growth factor β (TGF-β) pathways have been implicated in normal liver development as well as in cancer formation. In this study, we assessed the effect of the TGF-β signaling pathway on liver tumors induced by Pten (phosphatase and tensin homologue) loss. Inactivation of only the TGF-β receptor type II, Tgfbr2, in the mouse liver (Tgfbr2(LKO)) had no overt phenotype, while inactivation of Pten alone (Pten(LKO)), resulted in the formation of both hepatocellular carcinomas (HCC) and cholangiocarcinomas (CC). Interestingly, deletion of both Pten and Tgfbr2 (Pten(LKO);Tgfbr2(LKO)) in the mouse liver resulted in a dramatic shift in tumor type to predominantly CC. Assessment of the PI3K/PTEN/AKT pathway revealed increased phosphorylation of AKT and GSK-3β in both the Pten(LKO) and Pten(LKO);Tgfbr2(LKO) mice, suggesting that this pathway is constitutively active regardless of the status of the TGF-β signaling pathway. However, phosphorylation of p70 S6 kinase was observed in the liver of all three phenotypes (Tgfbr2(LKO), Pten(LKO), Pten(LKO);Tgfbr2(LKO)) indicating that the loss of Tgfbr2 and/or Pten leads to an increase in this signaling pathway. Analysis of markers of liver progenitor/stem cells revealed that the loss of TGF-β signaling resulted in increased expression of c-Kit and CD133. Furthermore, in addition to increased c-Kit and CD133, Scf and EpCam expression were also increased in the double knock-out mice. These results suggest that the alteration in tumor types between the Pten(LKO) mice and Pten(LKO);Tgfbr2(LKO) mice is secondary to the altered regulation of stem cell features induced by the loss of TGF-β signaling.